2023
DOI: 10.1021/acsapm.3c00560
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulated Diepoxy-Functionalized Ionic Liquids to the Design of Self-Healable Epoxy Networks

Abstract: An extrinsic self-healing mechanism based on microencapsulated healing agents represents an original way to produce self-healable thermosetting materials without modifying the structural architecture of the co-monomers. In this work, self-healing was achieved through poly(melamine–formaldehyde) (PMF) microcapsules containing a polymerizable diepoxidized ionic liquid monomer denoted as ILEM. First, a synthetic route to design ILEM@PMF microcapsules via in situ polymerization was developed and optimized through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Meanwhile, all these changes indicate that the generated ionic interactions can stand the temperature up to 180°C. The rheological behavior of LIonomers tends toward more gel‐like behavior compared to the neat polymer due to (i) the ionic interactions generated between PhILs and polymer chains acting as crosslinkings restraining segmental motions 29,43 ; (ii) the gel‐like structure induced by introducing PhILs 21,44 ; (iii) the presence of ionic domains within LIonomers (Figure 5). 1,10,40–42,45 On the other hand, the increase of MA content in the matrix causes a decrease of the viscosity (L‐P + DEP‐10 > LB1‐P + DEP‐10).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, all these changes indicate that the generated ionic interactions can stand the temperature up to 180°C. The rheological behavior of LIonomers tends toward more gel‐like behavior compared to the neat polymer due to (i) the ionic interactions generated between PhILs and polymer chains acting as crosslinkings restraining segmental motions 29,43 ; (ii) the gel‐like structure induced by introducing PhILs 21,44 ; (iii) the presence of ionic domains within LIonomers (Figure 5). 1,10,40–42,45 On the other hand, the increase of MA content in the matrix causes a decrease of the viscosity (L‐P + DEP‐10 > LB1‐P + DEP‐10).…”
Section: Resultsmentioning
confidence: 99%
“… 1,10,40–42,45 On the other hand, the increase of MA content in the matrix causes a decrease of the viscosity (L‐P + DEP‐10 > LB1‐P + DEP‐10). Due to the fact that more MA groups are available to generate more interactions while shortening the length of ionic branched chains made from cation‐anion pairs association 43 . Less crosslinking points and/or clusters lead to the decrease of the viscosity of blends.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from those very low T g materials, Kammakakam et al reported self-healing for aromatic polyamides possessing imidazolium groups in their backbone with T g of 130–160 °C. Additionally, ionic groups were exploited for self-healing in the form of ionic liquids, acting as solvents in microcapsules, and ILs were reported to catalyze the reactions of covalent adaptable networks (CAN), cross-linked polymers that can be reprocessed via dynamic bond exchanges. These dynamic bonds can stem from a variety of functional groups, each with its own drawbacks and advantages.…”
Section: Introductionmentioning
confidence: 99%